REKONSTRUKSI EPISTEMOLOGI GAYA KEPEMIMPINAN PENDIDIKAN: TELAAH FILSAFAT PENDIDIKAN ATAS PRAKTIK KEPEMIMPINAN DI SMP TERPADU CENDEKIA INSANI TAHUN 2016–2020 - Halimatus Sa’diyah (Jurnal Pendidikan Islam, 2025)
This study aims to reconstruct the epistemology of educational leadership by examining educational philosophy within the leadership practices of a female school principal with a Master’s background in science education at SMP Terpadu Cendekia Insani Situbondo during the 2016–2020 period. Employing a qualitative approach and an intrinsic case study design, the research analyzes data obtained through in-depth interviews, participatory observation, and documentation. The findings reveal that the leadership style implemented integrates scientific rationality with humanistic and spiritual values, resulting in a collaborative, participatory, and reflective leadership pattern. The epistemological reconstruction that emerges underscores that educational leadership is not merely technical or administrative, but a reflective process involving values, context, and epistemological awareness. The study contributes to the development of a new perspective on educational leadership grounded in the integration of scientific knowledge and humanistic principles, while positioning educational philosophy as an analytical lens in leadership studies. These findings hold significant implications for educational policy development, principal training programs, and future research in reflective and contextual leadership.